2004
DOI: 10.2116/analsci.20.13
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Measurements of Polychlorinated Biphenyls Using Laser Ionization Time-of-Flight Mass Spectrometry

Abstract: Polychlorinated aromatic hydrocarbons include many hazardous compounds, 1-5 such as PCBs (polychlorinated biphenyls), PCDDs (polychlorinated dibenzodioxins), PCDFs (polychlorinated dibenzofurans), polyhexachlorobenzene and pentachlorophenol. For protection from such chemicals, it is necessary to rapidly monitor their concentrations. Especially in PCB disposal plants, pollution of the surrounding environment must be strictly prevented, giving a strong imperative for the development of real-time measurement tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
(9 reference statements)
0
11
0
Order By: Relevance
“…It was confirmed that a laser with a pulse duration of 100 ps clearly generated a stronger PCB ion signal than a 5 ns pulse laser, by a factor of more than 10. 43) New findings presented here include the e$cient trapping of laser-ionized PCB ions using the dynamic trapping time-of-flight mass spectrometry (TOFMS), as well as the simulation of electric field control conditions for e$cient trapping, and observation of the e#ectiveness of reducing the speed of the ions introduced into the trap apparatus. 41), 42) Evaluations of accuracy based on comparisons with the results of the conventional method (gas sampling/gas chromatography mass spectrometry; gas sampling/ GC-MS) demonstrated a coe$cient of variation of ῌ30῍.…”
Section: )῏68)mentioning
confidence: 99%
“…It was confirmed that a laser with a pulse duration of 100 ps clearly generated a stronger PCB ion signal than a 5 ns pulse laser, by a factor of more than 10. 43) New findings presented here include the e$cient trapping of laser-ionized PCB ions using the dynamic trapping time-of-flight mass spectrometry (TOFMS), as well as the simulation of electric field control conditions for e$cient trapping, and observation of the e#ectiveness of reducing the speed of the ions introduced into the trap apparatus. 41), 42) Evaluations of accuracy based on comparisons with the results of the conventional method (gas sampling/gas chromatography mass spectrometry; gas sampling/ GC-MS) demonstrated a coe$cient of variation of ῌ30῍.…”
Section: )῏68)mentioning
confidence: 99%
“…E-mail: shinsaku_dobashi@mhi.co.jp AREF) maintains a high internal vacuum of about 10 -8 Torr by means of turbo-molecular pumps. 8 The measurement sample is supplied to the apparatus in the form of an ultrasonic molecular beam, through the use of a pulse valve (R. M. Jordan Co., PSV) and a 5 mm diameter skimmer. The pulse valve (orifice, 0.5 mm) delivered 50 µs duration gas pulses at 10 Hz into the vacuum chamber.…”
Section: Tofms Measurement Equipmentmentioning
confidence: 99%
“…The pulse duration of this laser equipment was 5 ns, with a pulse repetition rate of 10 Hz and an output of 5 mJ/pulse at 266 nm. 7,8 Measurement samples Figure 2 shows the chemical structures for monochlorinated benzene and PCBs. The m/z of MCB, 2 -4 chlorinated PCBs are 112, 222, 256 and 290, respectively.…”
Section: Laser Ionization Opticsmentioning
confidence: 99%
See 2 more Smart Citations